2018
DOI: 10.1590/rbz4720170035
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of soybean meal for urea in diets based on deferred buffelgrass hay for feedlot sheep

Abstract: The objective of this study was to evaluate the effect of substituting soybean meal for urea in diets based on deferred buffelgrass on the performance of feedlot sheep. Thirty mixed-breed sheep with an average initial body weight of 17±1.5 kg were distributed in a completely randomized design in which the experimental treatments consisted of five diets with six replicates. Diets were composed of deferred buffelgrass plus concentrates and calculated to be isoproteic. Treatments were represented by the substitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Different from other grasses, buffel grass has a low lignin content (4.13%) (Table 1) because of its rapid growth and flowering after the rainy period. Indeed, several studies have shown that lignin is not synthesized in large amounts during its regrowth (Moreira et al ., 2007; Perazzo et al ., 2017; Pereira et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Different from other grasses, buffel grass has a low lignin content (4.13%) (Table 1) because of its rapid growth and flowering after the rainy period. Indeed, several studies have shown that lignin is not synthesized in large amounts during its regrowth (Moreira et al ., 2007; Perazzo et al ., 2017; Pereira et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%